Dietary energy and protein for growing pigs : 1. performance and carcass composition - Thomke, Sigvard; Madsen, Arne; Mortensen, Hans Peder; Sundstol, Frik; Vangen, Odd; Alaviuhkola, Timo; Andersson, Kristina (Scandinavian University Press, 1995)
In a joint Nordic project,four experiment with a total of 880 gro wing pigs following the same outline were conducted in Denmark, Norway, Finland and Sweden. In three of these experiments the animals were fed individually. Five dietary treatments were investigated with respect to effect on performance, arcass composition and leg condition by entire or partial dissection. Thereatments were: (1) restricted standard feeding as a reference in al experiments; (2) ad libitum feeding with protein (amino acid) cocentrations according to recommended allowances (RA); (3)s in (2) bt RA increased by 10% (RA+10%); (4) as a (2) but RA lowered by 10% (RA-10%), or (5) the most common restricted feeding scale recommended in the individual countries, thus being different from expeiment to experiment. Compared with the restricted standard feeding, for wch daily feed intake and daily gainin the weight range 23-100 kg averad 2.07 kg and 750 g, respectively (rel. value 100), the corresponding ean values for the ad libitumfed animals were 119 and 120, respectively (p<0.001). Ad libitum compard with restricted feeding lowered carcass meat percentage units (p<0.05-0.01). eeding regimen did not affet leg codition. in the weightrance 23-60 kg, treatment RA-10% relted in a slight decese in performance and so in a slighty lowered carcass quality at 100 kg. On restrict feeding, females and casrated males performed equally, but arcass meat percentae of the former exeeded that of the latter by 2.3 percentage units (p<0.001). Daily feed intak and weight gain of ad libitum fed castrated males exceeded the values offemales by 11% and 9%, respectively (p<001). Sex did not aect feed efficiency of ad libitum fed animals. Castrated males showed a poorer hind leg condition than females (p<0.01). Carcass meat percentage s higher in restricedly fed ta in ad libitum d animals. The difference was 0.7 and 1.8 percentage units fr females and castrated males, respectively. A main conclusion is that the daily feed intake is a major factor in the control of the development of the animals and also for the extent of fat depostion.
Keywords: ad libitum feeding; carcass composition; energy intensity; meat percentage; protein level